Mindfulness, Compassion, and Resilience among young adults - Annalakshmi, Narayanan (Asia Pacific Journal of Social Science Research, 2022)
Abstract: Mindfulness interventions are effective not only in alleviating existing psychopathologies but also in promoting resilience. However, little is studied about the potential pathways that explain these relationships. The present correlational study attempts to examine the mediating pathways of mindfulness and resilience using a sample of 300 college students (Males=150; Females=150), with the mean age 19.5 years, majoring in the engineering discipline. The participants completed self-report measures of mindfulness, gratitude, self-compassion, communal orientation, compassionate love for humanity, love, and care for nature, and resilience. ANOVA, multiple regression, and parallel mediation models were used to analyze the data. A bootstrapped mediation model confirmed a significant indirect effect mediated through self-compassion, communal orientation, and love and care for nature on resilience. The findings underscore the potential benefits of compassion in promoting resilience. The implications for research and practice include designing a compassion-focused program tailored for young adults to enhance resilience in them.